Collaboration-Based BIM Model Development Management System for General Contractors in Infrastructure Projects - Yu-Cheng Lin; Nan-Hai Lo; Hsin-Tzu Hu; Ya-Ting Hsu (Journal of Advanced Transportation)
For mass rapid transit (MRT) projects, the characteristics of MRT engineering include large scopes, long durations, complex interfaces, significant requirements for management, and complicated coordination and cooperation. Owing to the complexity of these projects, the use of building information modeling (BIM) technology will be necessary and helpful to improve construction management. The increasing application of BIM in the architecture, engineering, and construction (AEC) industries has strengthened the need for effective construction management for general contractors (GC) for BIM implementation during the construction phase. Collaboration-based BIM model development for GCs typically involves relevant participants from different fields during the construction phase of MRT projects. However, collaboration-based BIM model development tasks often create numerous practical problems (e.g., reworks and errors regarding BIM model development). As the BIM manager and engineers for the general contractor who handle BIM model development are located in different departments and different office locations in MRT construction projects, a centralized platform is needed to share the latest real-time BIM model developments for related participants. Effective collaboration-based BIM model development management (CBMDM) is therefore essential for GCs to obtain accurate BIM models before the implementation of BIM-related applications. While the latest information for collaboration-based BIM model development should be updated and tracked effectively for CBMDM for related participants during the development process, in practice, GCs lack systematic approaches and information management platforms for use in CBMDM tasks. Thus, this study proposes a novel approach and develops an information system to manage and track all CBMDM tasks for GCs during the BIM development process. The purpose of this study is to develop a CBMDM system to improve the efficiency of sharing and tracking information for CBMDM activities. The research scope of this study is to propose an approach and system for CBMDM work in large-scale construction and infrastructure projects. The CBMDM system assists users by providing workflow management of CBMDM tasks for BIM engineers and managers so users can manage all BIM model development tasks effectively. The proposed system can also be utilized for other types of large-scale construction projects for CBMDM tasks. Furthermore, to understand its effectiveness, the proposed CBMDM system is applied to a case study of an MRT project in Taiwan. Finally, the major practical advantages, disadvantages, and limitations of the system are identified for infrastructure projects.